Des œuvres en morceaux et des trous sur les murs. La difficulté d’écrire la vie des œuvres du Pérugin au XIXe siècle - Éloïse Dumas (Les Cahiers de l'École du Louvre)
Among the thousands of works brought back to Paris by Napoleon’s troops, twenty-six were attributed to Perugino and almost all of them came from Perugia. The geography of the works was turned upside down. Once in France, the paintings were dispersed to provincial museums, and the curators of the Italian States gave up on recovering them in 1816, concentrating on those in the Louvre. Those from Perugia never returned to the Louvre but were kept for the new Vatican Pinacoteca. Entry into the museum represented a turning point in the life of the works. That was when a process of material, intellectual and emotional appropriation began. In Perugia, their absence gave way to a memory that froze scholarship and contributed to the crystallisation of the collective consciousness. This upheaval in the life of the objects had a profound effect on their biography, which historians wrote throughout the century, reuniting the dismembered altarpieces in books.